KEBIJAKAN DIVIDEN DAN PEMBELIAN KEMBALI SAHAM: PENGUJIAN LIFE CYCLE THEORY - Devi Indriyani; Dwi Ratmono (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to examine the influence of life cycle theory and leverage on dividen policy and buyback. Life cycle is proxied by RETA (retained earning to total asset). This study purposes hypothesis that RETA have positive influence on dividen policy and buyback whereas leverage have negative influence on dividend policy and buyback. The population of this research is all of listed firms in Indonesia Stock Exchange in year 2009-2012, exclude financial firms. Sampling method used is purposive sampling. Logistic regression used to be analysis technique. The final amounts of sample are 520. Result of this study show that retained earning to total asset have positively significant influenced on probability of dividen distributing. Retained earning to total asset have no significance on probability of buyback action. Leverage have no significance on dividend policy but have negative influence on buyback. The finding of this study supports life cycle theory.